Impact of Differentiated Learning Strategies on Student Resilience and Academic Performance at State Junior High School - Ely Wahyuni Hidayati; Eges Triwahyuni; Ahmad Zaki Emyus (Jurnal Penelitian Pendidikan IPA, 2025)
Differentiated learning strategies aim to improve students' learning outcomes and resilience in facing academic challenges. This study aimed to assess the efficacy of the strategy among ninth grade students at SMP Negeri Gumukmas. This study used a quasi-experimental design with a total of 98 students, divided into intervention and control groups of 49 students each. The instruments used consisted of a learning outcome test sheet developed from the RPP and grids, a learning resilience observation sheet based on Ann Masten indicators, and a validated and reliable questionnaire. The data were analyzed using the Friedman test due to the non-normal distribution of the data. The results showed a significant increase in learning outcomes and resilience for students in the intervention group compared to the control group, with a p-value of less than 0.05. These findings reinforce that differentiated learning strategies are effective in improving learning resilience and improving student learning outcomes.